Measuring The Level of Job Performance of Workers In The Banking Sector - الكنج, ربى (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of the research is to determine the level of job performance of workers in private Syrian banks from the point of view of officials (director, assistant director, heads of departments and divisions), according to the following performance indicators: knowledge of job requirements, quality of work, amount of work performed, perseverance and confidence. The research was based on the descriptive and analytical approach. The current research targeted (11) banks, (66) questionnaires were distributed, and (59) questionnaires were retrieved from them, with a response rate of (89.39%). The results showed that the level of job performance of workers in the banks under study is high on the overall level, and with regard to the sub-indicators of performance.